In vitro regeneration performance of Corchorus olitorius - Hoque, M; Nasiruddin, KM; Haque, GKMN; Biswas, GC (Journal of the Bangladesh Agricultural University, 2010)
The experiment was conducted during May to December 2008 in the Biotechnology Laboratory of Bangladesh Agricultural University, Mymensingh to observe the callus induction, regeneration potentiality and to establish a suitable in vitro plantlet regeneration protocol of Corchorus olitorius. MS medium supplemented with different phytohormone concentrations and combinations were used to observe the callus induction, shoot regeneration and root formation ability of the cotyledon with attached petiole derived explant of three genotypes viz. O-9897, O-72 and OM-1. The highest callus induction (92.85%) was observed in O-9897 followed by O-72 (82.14%) in the MS media supplemented with 2.5 mg/L BAP + 0.5 mg/L IAA. Genotype O-9897 in MS media supplemented with 2.5 mg/L BAP + 0.5 mg/L IAA produced the highest percentage of shoot regenerants (83.33%) followed by O-72 (75.00%) in the media supplemented with 2.5 mg/L BAP + 0.5 mg/L IAA. The root formation from regenerants was the best on halfstrength of MS media supplemented with 0.6 mg/L IBA in genotype O-9897 (45.00%). The in vitro regenerated plantlets from the genotypes O-9897 could be established in the field. Therefore, the genotypes O-9897 of C. olitorius in MS media supplemented with 2.5 mg/L BAP + 0.5 mg/L IAA could be used for callus induction and shoot regeneration. Keywords: Regeneration; Phytohormone; Corchorus olitorius DOI: 10.3329/jbau.v8i1.6390 J. Bangladesh Agril. Univ. 8(1): 1-6, 2010